Clinical outcomes of polyvalent immunoglobulin use in solid organ transplant recipients: A systematic review and meta‐analysis. Issue 6 (23rd April 2019) - Bourassa‐Blanchette, Samuel; Knoll, Greg A.; Hutton, Brian; Fergusson, Nicholas; Bennett, Alexandria; Tay, Jason; Cameron, D. William; Cowan, Juthaporn
Abstract: Polyvalent immunoglobulin is commonly used for desensitization and treatment of antibody‐mediated rejection in kidney transplantation but its impact on other outcomes is not known. This systematic review investigated the impact of immunoglobulin prophylaxis on infection, rejection, graft loss, and death following kidney transplantation. A comprehensive literature search located 18 studies (n = 8 randomized controlled trials). None examined the effect of immunoglobulin prophylaxis in transplant recipients with hypogammaglobulinemia. Quality of included studies was variable with high to very high risk of bias. In the randomized trials, immunoglobulin use did not reduce cytomegalovirus infection (OR 0.68 [0.39, 1.21]; 6 studies, n = 295), rejection (OR 0.96 [0.50, 1.82]; 4 studies, n = 187), or graft loss (OR 1.03 [0.46, 2.30]; 6 studies, n = 265). In non‐randomized studies, immunoglobulin did not reduce cytomegalovirus infection (OR 0.63 [0.20, 1.94]; 6 studies, n = 361) or death (OR 1.32 [0.05, 38.79]; 3 studies, n = 222) but reduce rejection (OR 0.47 [0.24, 0.94]; 4 studies, n = 268) and graft loss (OR 0.15 [0.05, 0.43]; 2 studies, n = 118). Data were scarce and sample size of current evidence was small. Adequately powered randomized trials are needed to determine if immunoglobulin is an effective intervention to reduce infection, rejection, graft loss, or death following kidney transplantation with and without hypogammaglobulinemia.